Analytical Approaches to Verify Food Integrity: Needs and Challenges. (4th December 2019) - Stadler, Richard H; Tran, Lien-Anh; Cavin, Christophe; Zbinden, Pascal; Konings, Erik J M
Abstract: A brief overview of the main analytical approaches and practices to determine food authenticity is presented, addressing, as well, food supply chain and future requirements to more effectively mitigate food fraud. Food companies are introducing procedures and mechanisms that allow them to identify vulnerabilities in their food supply chain under the umbrella of a food fraud prevention management system. A key step and first line of defense is thorough supply chain mapping and full transparency, assessing the likelihood of fraudsters to penetrate the chain at any point. More vulnerable chains, such as those where ingredients and/or raw materials are purchased through traders or auctions, may require a higher degree of sampling, testing, and surveillance. Access to analytical tools is therefore pivotal, requiring continuous development and possibly sophistication in identifying chemical markers, data acquisition, and modeling. Significant progress in portable technologies is evident already today, for instance, as in the rapid testing now available at the agricultural level. In the near future, consumers may also have the ability to scan products in stores or at home to authenticate labels and food content. For food manufacturers, targeted analytical methods complemented by untargeted approaches are end control measures at the factory gate when the material is delivered. In essence, testing for food adulterants is an integral part of routine QC, ideally tailored to the risks in the individual markets and/or geographies or supply chains. The development of analytical methods is a first step in verifying the compliance and authenticity of food materials. A next, more challenging step is the successful establishment of global consensus reference methods as exemplified by the AOAC Stakeholder Panel on Infant Formula and Adult Nutritionals initiative, which can serve as an approach that could also be applied to methods for contaminants and adulterants in food. The food industry has taken these many challenges aboard, working closely with all stakeholders and continuously communicating on progress in a fully transparent manner.